The Influence Of Opinion Leadership On Purchase Intentions For Organic Food Products In Jakarta - Nuki Ardiansyah; Dewi Fatima; Agastya Nugraha; Jonathan Suherman; Ridho Ryzkita (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This paper proposes a conceptual model by extending the theory of planned behavior (TPB) by adding an opinion leader dimension to overseas the purchase intention in organic food in Jakarta. The Data was gathered from a survey comparing 283 corespondents, who live in Java. The finding support the original TPB plus perceived quality, brand loyalty and opinion leadership were also the factor of purchase intention. Perceived behavior control is the most important key to forecasting the purchase intention. No significant output that had been established brand awareness and brand image on purchase intention. The result produced useful information for marketers for helping to gain a health oriented segment for organic food in Indonesia. The added dimensions of opinion leader further enhance knowledge in organic food.